Developing rates for small systems (American Water Works Association, 2004)
Annotation "AWWA Manual M54, Developing Rates for Small Systems, focuses on the unique attributes of small systems as related to financial planning and rate design. Recognizing that small systems may be faced with resource and data limitations, this manual can be used as a guide in the development of financial plans, revenue requirements, rate analyses, and rate design. Managers and operators of small systems and their advisors (financial, accounting, and engineering professionals) should find this manual useful in preparing water rates that recover costs using generally accepted cost-based practices."--BOOK JACKET.Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.
Includes index.
Keywords: Water-supply -- Rates.; elektronické knihy; electronic books